2020
DOI: 10.1017/s0007114520003852
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and associations with BMI in low-income, ethnic minority youth in the USA according to baseline data from four randomised controlled trials

Abstract: Few studies have derived data-driven dietary patterns in youth in the United States (US). This study examined data-driven dietary patterns and their associations with BMI measures in predominantly low-income, racial/ethnic minority US youth. Data were from baseline assessments of the four Childhood Obesity Prevention and Treatment Research (COPTR) Consortium trials: NET-Works (N=534; 2–4-year-olds), GROW (N=610; 3–5-year-olds), GOALS (N=241; 7–11-year-olds), and IMPACT (N=360; 10–13-year-olds). Weight and heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Studies have shown that children from families with low incomes generally consume less healthy diets and have higher BMI (Body Mass Index) z-scores [16,17]. Several studies emphasize the stronger impact of unhealthy food environments on the weight status of children from poor families [12,18].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that children from families with low incomes generally consume less healthy diets and have higher BMI (Body Mass Index) z-scores [16,17]. Several studies emphasize the stronger impact of unhealthy food environments on the weight status of children from poor families [12,18].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies in the United States have focused on investigating associations between specific dietary factors and chronic diseases [12][13][14].The association between the adherence dietary patterns and total mortality and mortality due to cancer in the general population is still limited. Dietary patterns condense information about food consumption, reflect diet composition, and capture the overall effect of dietary exposures on health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies evaluated the effect of dietary patterns and mortality in other countries [8][9][10][11]. In the United States, studies have shown the association between adherence to specific dietary patterns and chronic diseases, including obesity [12,13], cardiovascular disease, and diabetes [14]. Moreover, only a few studies have investigated the relationship between specific dietary patterns and total mortality [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%